Math CentralQuandaries & Queries


Question from Kieran, a student:

How could I work this out please

f(x)= 3xsquared - 4x + 2

if f(2x)


Let me try a similar example.

g(x) = 4x2 - 3x + 7, find g(3x).

What you need to do to find g(3x) is to take the expression for g(x), replace x by 3x and simplify. I get

g(3x) = 4(3x)2 - 3(3x) + 7.

Since (3x)2 = (3x)(3x)= 9x2 this simplifies to

g(3x) = 4(9x2) - 9x + 7 = 36x2 - 9x + 7.

Now try your problem.



About Math Central


Math Central is supported by the University of Regina and The Pacific Institute for the Mathematical Sciences.
Quandaries & Queries page Home page University of Regina PIMS